2012
DOI: 10.1111/crj.12001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of using exhaled NO in asthma diagnosis and management

Abstract: Background: Current guidelines recommend tailoring of asthma management according to disease control, which is largely defined by increased symptoms and deterioration in lung function. These features do not reflect the severity nor the type of the asthmatic airway inflammation. Fractional exhaled nitric oxide (FENO) is a simple, non-invasive and cost-effective online test applicable in both adults and children. In addition to symptoms and lung function measurements, FENO reflects airway eosinophilia and hence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 166 publications
(158 reference statements)
2
24
0
2
Order By: Relevance
“…NO is synthesized by various cells through the oxidation of L-arginine by NO synthase. In asthma, inducible NO synthase expression is upregulated by activating STAT-6 through interleukins 4 and 13 produced by T helper 2 cells, mast cells and eosinophils [4,21]. Thus, eNO directly signals the proinflammatory cytokine mechanisms of central importance in the pathophysiology of asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO is synthesized by various cells through the oxidation of L-arginine by NO synthase. In asthma, inducible NO synthase expression is upregulated by activating STAT-6 through interleukins 4 and 13 produced by T helper 2 cells, mast cells and eosinophils [4,21]. Thus, eNO directly signals the proinflammatory cytokine mechanisms of central importance in the pathophysiology of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, fractional eNO (FeNO) has become a valuable tool for the diagnosis and monitoring of asthma in childhood [4]. Previous studies investigating relationships between FeNO and AHR have shown inconsistent results and the correlations were generally low [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It can be performed using different techniques, including chemiluminescence, electrochemical detection, and laser spectroscopy [20]. Online and offline methods are available for collecting and analyzing FE NO , but only the single breath online method (SBOL) has been fully standardized and it is now the gold standard for FE NO measurement in children who are able to cooperate [21].…”
Section: Exhaled Nitric Oxide (Fe No )mentioning
confidence: 99%
“…In particular, IL-4 and IL-13 induce an upregulated epithelial iNOS expression. Exhaled NO directly reflects Th2-mediated proinflammatory cytokine mechanisms [20,29].…”
Section: Fe No In Asthma Diagnosis and Inhaled Corticosteroids (Ics) mentioning
confidence: 99%
“…NO is an excellent surrogate marker of inhaled corticosteroid (ICS)-sensitive local type-2 cytokine-driven inflammatory mechanisms, which are of central importance in allergic airway inflammation [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%